Global precarious employment and health inequalities: working conditions, social class, or precariat? - Carles Muntaner (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2016)
Abstract: Changes in employment conditions since the 1980s have been referred to as precarious employment, and terms like flexible, atypical, temporary, part-time, contract, self-employed, irregular, or non-standard employment have also been used. In this essay I review some of the current critiques to the precarious employment construct and advance some potential solutions for its use in epidemiology and public health.